Data underpinning "Interpass Rolling of Ti-6Al-4V Wire + Arc Additively Manufactured Features for Microstructural Refinement" - Colegrove, Paul; McAndrew, Anthony (Cranfield University, 2018)
Data set for grain size graphs.
Keywords: 'Additive Manufacturing Technologies'; 'Additive Manufacturing'; 'Materials Engineering not elsewhere classified'